Percutaneous endoscopic lumbar discectomy as a treatment for lumbar disc herniation linked with posterior ring apophysis separation - Li, Ran; Zhou, Hongyou; Han, Hao; Fu, Dongming; Zhan, Zihao; Meng, Bin (Frontiers in Surgery, 2023)
Background: Lumbar disc herniation (LDH) linked with posterior ring apophysis separation (PRAS) is a rare and distinct subset of disc herniation. Few studies have evaluated the clinical efficacy of percutaneous endoscopic lumbar discectomy (PELD), which is a procedure used to treat LDH linked with PRAS. Objectives: To evaluate the clinical efficacy and safety of PELD in the treatment of LDH linked with PRAS. Methods: Patients who met inclusion criteria (n = 67; 40 males and 27 females) underwent PELD. General and operation‐related information and perioperative complications of the patients were recorded. Clinical efficacy was measured using the Visual Analog Scale (VAS) and Oswestry Disability Index (ODI) during the follow‐up period. Results: The mean operation time was 118.04 ± 19.31 min and the mean blood loss was 22.84 ± 15.89 ml. The VAS and ODI scores continued to improve immediately after the surgery to the last follow‐up. Four patients experienced postoperative complications i.e., herniation recurrences. The conditions of the patients with the complications improved after treatment. Conclusions: PELD has reliable efficacy and safety in the treatment of LDH linked with PRAS.